Zoneamento para uso de cultivares de soja no Brasil conforme o grupo de maturidade - Ferreira, Lenio Urzeda (2018)
Due to the sensitivity of soybeans to environmental variations, especially to the temperature and photoperiod, the development and recommendation of cultivars need to be regionalized through environmental groupings or zones. The objectives of this study were: i) to understand the adaptive levels of soybean by maturation group, over the cropping regions in Brazil; ii) to prepare a recommendation map of soybean cultivars, according to their maturity groups, in order to optimize the grain yield; and iii) to understand the spatio-temporal adaptive variations of the cultivars according their relative maturity groups. Data from variety trials, named in Brazil as “value for cropping and use” (VCU) trials, conducted in 175 locations, at growing seasons from 2013/14 to 2016/17, were used. The trials were distributed in all the soybean producing regions of the country. The assessed genotypes were grouped in ranges of relative maturation, being outstood the midpoint of maturation of the most yield genotypic group as a reference for each location. Then, the regression-kriging method was used for the spatialization of the relative maturities associated to the cultivars with higher yield adaptation. A spatio-temporal analysis was performed aiming to verify possible adaptive differentiated trends of the cultivars, according to the relative maturation groups, over the cropping seasons. The results showed that soybean cultivars, according to their relative maturation, present different yield adaptive levels in each geographical cropping region. In addition, concerning the yield adaptation, the cultivars with earlier maturation (belonging to lower maturity groups – e.g., 5.5 to 6.5) showed to be more suited to regions of high latitudes, while those of higher relative maturity groups were more suited to lower latitude regions. In general, according to the maturity groups, the yield adaptive levels of the cultivars have presented variations as a function of time, in order to favor earlier cultivars in regions of lower latitude. The adaptation of late cultivars, with relative maturity between 8.5 and 9.5, has retreated to the extreme north of Brazil. In the subtropical region discrete temporal variations of the adaptive levels of the cultivars were verified. However, in the tropical region, considerable temporal changes were observed, mainly in favor of the earlier cultivars. Latitude and altitude were the predominant factors in the definition of yield adaptation of the cultivars, and the influence of altitude promotes discrete deflections in the adaptive zones determined by latitude, favoring the yield adaptation of earlier cultivars in higher elevation locations.